Planning and Preparation of Domicile Search: Array - Răduță, Mihai-Ionuţ (Journal of Danubian Studies and Research, 2021)
This article addresses the evidence of the search process both in terms of procedural and practical elements. Considering the quality of criminal investigator of the authors, this article mainly addresses the practical aspects and concrete situations encountered in the judicial practice. Also the specifications in this article can successfully guide the practitioners in the activity.